A relação entre a logística e compras no e-commerce para clientes de Araras-SP e região - OLIVEIRA, Andressa do Amaral Pinto Sabbadin de; COLADETTi, Sonia Regina Pratero (290, 2024)
Esta pesquisa abordou a relação entre a logística e compras no e-commerce, e seu impacto no processo decisório de compras dos consumidores em Araras-SP e região. O estudo enfatizou estratégias logísticas eficientes que melhoram a experiência do cliente, aumentam as vendas e mantêm a competitividade. Desafios como preços baixos, entregas rápidas e bom atendimento são cruciais para a decisão de compra do cliente. O objetivo do trabalho foi conhecer a relação existente entre logística e compras on-line, na modalidade de e-commerce B2C, por parte de consumidores de Araras-SP e região. A metodologia de pesquisa foi de abordagem qualiquantitativa e descritiva, quanto aos objetivos; houve pesquisa bibliográfica, pesquisa documental e o instrumento de coleta de dados foi um questionário on-line para consumidores de Araras-SP e região. A pesquisa revelou que a logística influencia o processo decisório de compras por e-commerce, em relação a fatores, tais como disponibilidade de horário e pontualidade na entrega, embora não sejam os únicos aspectos determinantes. E, também, destacou a necessidade de investimentos contínuos em tecnologia e otimização logística para melhorar a experiência de compra e evitar frustrações devido a atrasos.

This research examined the relationship between logistics and e-commerce purchases and its impact on the purchasing decision-making process of consumers in Araras, São Paulo, and the surrounding region. The study emphasized efficient logistics strategies that improve the customer experience, increase sales, and maintain competitiveness. Challenges such as low prices, fast deliveries, and good service are crucial to the customer's purchasing decision. The objective of this study was to investigate the relationship between logistics and online purchases in the B2C e-commerce modality from the perspective of consumers in Araras-SP and the surrounding region. The research methodology employed a combination of qualitative and quantitative approaches, with a descriptive focus on the objectives. This involved a comprehensive review of relevant literature, as well as documentary research. The data collection instrument was an online questionnaire administered to consumers in Araras-SP and the region. The research findings indicate that logistics plays a role in the decision making process for e-commerce purchases, particularly in relation to factors such as time availability and punctuality of delivery. However, it is important to note that these are not the only determining aspects. The study also highlights the need for continuous investment in technology and logistics optimization to improve the shopping experience and avoid frustration due to delays.
The relationship between logistics and e-commerce purchases for customers in Araras-SP and the surrounding region
Keywords: Comércio eletrônico; Satisfação do consumidor; Distribuição logística; Gestão e Negócios